1999
DOI: 10.1017/s1446788700000847
|View full text |Cite
|
Sign up to set email alerts
|

Inverse semigroups with zero: covers and their structure

Abstract: We obtain analogues, in the setting of semigroups with zero, of McAlister's covering theorem and the structure theorems of McAlister, O'Carroll, and Margolis and Pin. The covers come from a class C of semigroups defined by modifying one of the many characterisations of E-unitary inverse semigroups, namely, that an inverse semigroup is E-unitary if and only if it is an inverse image of an idempotent-pure homomorphism onto a group. The class C is properly contained in the class of all £*-unitary inverse semigrou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…In summary: if ⌺ has cardinality n, then w x in Theorem 9.5.6 of 9 it is proved that the tiling semigroup S S is a Rees quotient of a semigroup K , called a Kachel semigroup on n letters. 1 The n semigroup K may be embedded in the McAlister semigroup M , intron n w x duced in 8 .…”
mentioning
confidence: 99%
“…In summary: if ⌺ has cardinality n, then w x in Theorem 9.5.6 of 9 it is proved that the tiling semigroup S S is a Rees quotient of a semigroup K , called a Kachel semigroup on n letters. 1 The n semigroup K may be embedded in the McAlister semigroup M , intron n w x duced in 8 .…”
mentioning
confidence: 99%
“…In general, prehomomorphisms between inverse monoids are defined in terms of the natural order on the monoids, but the general definition is equivalent to condition (3) when the codomain is a group with zero adjoined. Implicit in [3] is the result that an inverse semigroup with zero is strongly E * -unitary if and only if it is a Rees quotient of an E-unitary inverse semigroup. This was made explicit with an easy proof in [29].…”
Section: Polygraph Monoidsmentioning
confidence: 99%
“…Since there are lots of finite E-unitary inverse semigroups and every Rees factor of such a semigroup is E * -unitary, [2], it follows that finite ∨-semilatticed inverse semigroups are very common. [Bulman-Flemming, Fountain, and Gould [2] have also shown that not every E * -unitary inverse semigroup is a Rees factor of an E-unitary inverse semigroup.]…”
Section: Introductionmentioning
confidence: 99%
“…[Bulman-Flemming, Fountain, and Gould [2] have also shown that not every E * -unitary inverse semigroup is a Rees factor of an E-unitary inverse semigroup.] A class of interesting examples of such semigroups is the following.…”
Section: Introductionmentioning
confidence: 99%